A D2D assisted multi‐hop data dissemination protocol for inter‐UAV communication. (4th May 2021) - Khan, Mohammad Zubair; Rahim, Muddasir; Javed, Muhammad Awais; Ghabban, Fahad; Ameerbakhsh, Omair; Alfadli, Ibrahim
Summary: Unmanned aerial vehicles (UAVs) are key components of future Internet of Things as they facilitate efficient data sensing and transmission. However, UAVs will be sparsely placed and data dissemination among UAVs is a challenge. In this regard, cellular users can help to propagate the data between UAVs by using multi‐hop device‐to‐device (D2D) communication. A key challenge for multi‐hop D2D communication to support inter‐UAV communication is to select optimal forwarding D2D nodes that reduce the communication delay. In this paper, we propose a multi‐hop data dissemination protocol for inter‐UAV communication using D2D‐enabled user equipment (UEs). We consider factors such as channel quality and queuing delay to find suitable forwarding D2D nodes. To improve reliability of transmission, the proposed protocol selects forwarding nodes within a forwarding area where packets can be successfully received. Simulation results verify that the proposed protocol can reduce end‐to‐end delay and improve reliability of multi‐hop UAV data dissemination. Abstract : In this paper, we propose a multi‐hop D2D data dissemination protocol for inter‐UAV communication with a goal to reduce the end‐to‐end delay. The central idea of the protocol is to reduce the forwarding time of packets at each hop by considering factors such as transmission time and queuing time.